SUGT1 is a prognostic biomarker and is associated with immune infiltrates in ovarian cancer - Linyan Ge; Xiu Liu; Lingyan Zhang; Jiaren Zhang; Guanghui Song (European Journal of Medical Research)
Abstract Background Ovarian cancer (OC) is a prevalent gynecological malignancy with a relatively dismal prognosis. The SGT1 homolog (SUGT1) protein, which interacts with heat shock protein 90 and is essential for the G1/S and G2/M transitions, was formerly thought to be a cancer promoter, but its precise role in OC remains unknown. Methods We conducted a comprehensive bioinformatics analysis of SUGT1 expression in patients with OC compared with their normal controls, including the data from the cancer genome atlas (TCGA), genotype–tissue expression (GTEx) databases, gene ontology (GO) analysis, Kyoto Encylopedia of Genes and Genomes (KEGG) analysis, gene set enrichment analysis (GSEA), single sample gene set enrichment analysis (ssGSEA). In addition, Kaplan–Meier (KM) analysis, univariate and multivariate Cox analyses were applied to investigate the prognostic role of SUGT1 in ovarian cancer. Furthermore, we validated the expression of SUGT1 in OC and normal tissues through immunohistochemistry. Results SUGT1 was significantly overexpressed in OC than in normal tissues. In addition, the GO, KEGG and GSEA analysis revealed that SUGT1 was associated with the functions related to immunoglobulin complex, antigen binding, immunoglobulin receptor binding, among others. Besides, ssGSEA demonstrated a positive correlation between SUGT1 expression and the abundance of T central memory cells, natural killer cells, and T gamma delta cells, although it showed a negative association with activated dendritic cells, cytotoxic cells, T cells, and T helper 1 cells. Subsequently, KM survival analysis revealed that high SUGT1 expression indicated a shorter overall survival, disease specific survival and progression free interval in OC patients. Univariate and multivariate Cox regression revealed that SUGT1 could serve as an independent risk factor for prognosis of patients with OC. Conclusions All these results of this study show that SUGT1 is an important molecular component in immune infiltration in OC and may have a new significant prognostic role in OC.